Oxidative damage: the mitochondria as a target - Salazar, James J. (Actualidades Biológicas, 2017)
Reactive oxygen species are constantly produced in aerobic cells as result of metabolic processes. Oxidative stress can also result from exposure to environmental toxins. Hydrogen peroxide, superoxide anion and hydroxyl radicals are major species produced during metabolism. The hydroxyl radical can react with vital cellular molecules, such as DNA and proteins, leading to oxidative damage. Cells have developed defense systems to survive to chronic exposure to reactive oxygen species. Chronic exposure to reactive oxygen species is associated with an increasing number of human diseases, neurodegeneration and aging processes. Currently, much attention is focused on the deleterious effects of reactive species on cells but the mechanisms and pathways involved in those effects need to be extensively investigated.